Financial distress risk in initial public offerings: How much do venture capitalists matter? - Megginson, William L.; Meles, Antonio; Sampagnaro, Gabriele; Verdoliva, Vincenzo (Journal of Corporate Finance, 2019)
Using a sample of 1593 US firms that go public between 1990 and 2007, we find that VC-backed IPOs experience less financial distress risk post-offering than do comparable non-VC-backed IPOs. After controlling for endogeneity, we find this is related to the screening done by VC-investors, who select firms with lower risk of financial distress and by VCs reducing risks when they finance portfolio firms. We find companies backed by more reputable VCs exhibit higher levels of financial distress risk even when they show superior operating performance, due to their highly levered capital structure and investment in relatively illiquid assets.